Exploring the socioeconomic factors associated with girl child marriage and its impact on pregnancy outcomes: A study from Malda District of West Bengal - Avijit Roy; Pradip Chouhan (Wolters Kluwer Medknow Publications, 2022)
Background: Child marriage is not a new phenomenon in India. The prevalence of child marriage remains high in many districts of West Bengal. Objectives: The present study aims to address socioeconomic factors associated with girl child marriage and its effect on selected pregnancy outcomes among women in the Malda district of West Bengal. Methods: The study is based on primary data, collected from the Manikchak CD block by adopting a random sample survey technique. The participants in the study consisted of 357 ever married women aged 15-49 years. Results: Multivariate analysis revealed that the prevalence of child marriage was substantially higher among women who had no formal education resided in the marginalized family. Similarly, educated parents were less likely to marry their daughter at an early age. Besides, the likelihood of miscarried or stillbirth, complications during pregnancy and delivery were significantly higher among those married <18 years than those married at 18 years or later. Conclusions: The findings of this study suggest preventing child marriage by increasing opportunities for girls' education and employment. The targeted approach should be made among rural and poor girls to reduce the vulnerability of child marriage.